Revisiting "An Apriori-based Approach for First-Order Temporal Pattern Mining" - de Amo, Sandra; Furtado, Daniel A.; Giacometti, Arnaud; Laurent, Dominique (Journal of Information and Data Management, 2010)
A lot of diﬀerent approaches related to sequential pattern mining have been proposed in the literature, since 2004, when the original paper was published in the proceedings of SBBD 2004. Among these approaches, we distinguish ﬁve main directions of research: (1) development of more eﬃcient methods for the classical sequential pattern mining problem, (2) sequential pattern mining with constraints, (3) multidimensional and multilevel sequential patterns, (4) temporal patterns speciﬁed by more general structures (tree and graph patterns), (5) temporal relational patterns with interval time attributes.